Activation of α7 nicotinic acetylcholine receptors increases intracellular cAMP levels via activation of AC1 in hippocampal neurons - Cheng, Qing (Neuropharmacology, 2015)
The activation of α7 nAChRs has been shown to improve hippocampal-dependent learning and memory. However, the molecular mechanism of α7 nAChRs’ action remains elusive. We previously reported that activation of α7 nAChRs induced a prolonged enhancement of glutamatergic synaptic transmission in a PKA-dependent manner. Here, we investigated any connection between the activation of the α7 nAChR and cAMP signaling in hippocampal neurons. To address this question, we employed a FRET-based biosensor to measure the intracellular cAMP levels directly via live cell imaging. We found that application of the α7 nAChR-selective agonist choline, in the presence of the α7 nAChR positive allosteric modulator PNU-120596, induced a significant change in emission ratio of F535/F470, which indicated an increase in intracellular cAMP levels. This choline-induced increase was abolished by the α7 nAChR antagonist MLA and the calcium chelator BAPTA, suggesting that the cAMP increase depends on the α7 nAChR activation and subsequent intracellular calcium rise. The selective AC1 inhibitor CB-6673567 and siRNA-mediated deletion of AC1 both blocked the choline-induced cAMP increase, suggesting that calcium-dependent AC1 is required for choline’s action. Furthermore, α7 nAChR activation stimulated the phosphorylation of synapsin, which serves as a downstream effector to regulate neurotransmitter release. Our findings provide the first direct evidence to link activation of α7 nAChRs to a cAMP rise via AC1, which defines a new signaling pathway employed by α7 nAChRs. Our study sheds light into potential molecular mechanisms of the positive cognitive actions of α7 nAChR agonists and development of therapeutic treatments for cognitive impairments.